The Mixed-Up Chameleon - Carle, Eric (New York HarperCollins, 1984)
A bored chameleon wishes it could be more like all the other animals it sees, but soon decides it would rather just be itself. Cutouts along the edges of the pages display various animals and colors.
Keywords: Chameleons -- Juvenile fiction; Self-acceptance -- Juvenile fiction